Pengaruh Model Pembelajaran Siklus Belajar 5E Berbantuan Media Gambar Terhadap Hasil Belajar IPA - ari aditia, made; Margunayasa, I Gede; kusmariatni, ni nyoman (Jurnal Ilmiah Sekolah Dasar, 2018)
The research aimed to determine the differences of Science learning outcomes between students who were given Learning Cycle 5E model with the help of picture media and students who were given conventional learning in the fifth-grade students in Cluster IV District of Gianyar, Gianyar regency in the academic year 2017/2018. This research was quasi-experimental design and used post-test only control group design. The population of this research was all of the fifth-grade students in Cluster IV District of Gianyar, Gianyar regency in the academic year 2017/2018 which consisted 131 people. Sampling used simple random sampling technique by lottery. The samples of this research were 17 fifth grade students of SD (Elementary) Negeri 3 Samplangan and 17 fifth grade students of SD (Elementary) Negeri 2 Beng. The student science score as the data of this research was collected by using the objective test in the form of multiple choice. The data obtained were analyzed by using descriptive statistics and inferential statistics (t-test). The result of t-test analysis obtained t count 4,01 and t table = 2,037. There were significant differences of Science learning outcomes between students who were given Learning Cycle 5E model with the help of picture media and the students who were given conventional.